Psychological pathways from childhood sexual and physical abuse to HIV/sexually transmitted infection outcomes among homeless women: The role of posttraumatic stress disorder and borderline personality disorder symptoms. (October 2013) - Houston, Eric; Sandfort, Theo GM; Watson, Kalycia T; Caton, Carol LM
This study examines the psychological factors linking childhood abuse and HIV/sexually transmitted infection outcomes among 190 single homeless women in New York City. Participants were assessed for mental health symptoms, sexually transmitted infections, and exposure to childhood sexual and physical abuse. Findings indicate that the relationship between childhood abuse and HIV/sexually transmitted infection diagnoses during adulthood is mediated by a combination of posttraumatic stress disorder and borderline personality disorder symptoms. Screening single homeless women who report childhood abuse histories for symptoms of both disorders may aid in the identification of individuals particularly vulnerable for HIV infection. Implications for clinical interventions are discussed.